1989
DOI: 10.1128/jb.171.1.483-487.1989
|View full text |Cite
|
Sign up to set email alerts
|

Physiological studies of the regulation of beta-lactamase expression in Pseudomonas maltophilia

Abstract: The kinetics of j-lactamase induction in Pseudomonas maltophilia 1ID1275/873 were investigated. Upon induction with ,3-lactam antibiotics, a correlation was seen between the increase in specific P-lactamase activity and the generation time, as well as the concentration of inducer in the medium. The specific P-lactamase activity increased slowly within the first 0.5 generation and then more rapidly; it decreased regularly after about 2 generations of growth in the presence of inducer. This decrease could presum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
5
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Rosta and Mett found that total induced ␤-lactamase activity in S. maltophilia decreases at a rate of 50% per generation after the maximal peak (15). In the present study, a difference between the induction of L1 and that of L2 was apparent.…”
supporting
confidence: 44%
See 3 more Smart Citations
“…Rosta and Mett found that total induced ␤-lactamase activity in S. maltophilia decreases at a rate of 50% per generation after the maximal peak (15). In the present study, a difference between the induction of L1 and that of L2 was apparent.…”
supporting
confidence: 44%
“…The induced ␤-lactamase activity has been shown to be linearly correlated to the inducer concentration for Pseudomonas aeruginosa and S. maltophilia (13,15). In the present study, a roughly linear correlation was observed with KJ⌬L2 but not with KJ⌬L1.…”
supporting
confidence: 41%
See 2 more Smart Citations
“…Resistance to these agents is by a combination of intrinsic and acquired determinants. Resistance to ␤-lactams is primarily intrinsic, mediated by two inducible ␤-lactamases, L1 and L2 (10,18,(21)(22)(23). L1 is a Zn 2ϩ -dependent metalloenzyme that hydrolyzes virtually all classes of ␤-lactams, including penicillins, cephalosporins, and carbapenems but excluding monobactams (9,18,22,30), while L2 is a serine active-site cephalosporinase (23, 31).…”
mentioning
confidence: 99%